Nutritional, Functional, and Technological Characterization of a Novel Gluten- and Lactose-Free Yogurt-Style Snack Produced With Selected Lactic Acid Bacteria and Leguminosae Flours - Pontonio, Erica; Raho, Susanna; Dingeo, Cinzia; Centrone, Domenico; Carofiglio, Vito Emanuele; Rizzello, Carlo Giuseppe (Frontiers in Microbiology, 2020)
Aiming at meeting consumers’ requirements for healthy foods, dietary needs (vegetarianism, lactose- and gluten-free), as well as the nutrition recommendations of the Health Authorities in terms of protein, fibers and bioactive compounds, the present study proposes a novel yogurt-style snack made with plant-derived ingredients. The biotechnological protocol includes the fermentation of a thermal-treated blend of cereal and legume flours by the selected lactic acid bacteria (LAB) Lactoplantibacillus plantarum DSM33326 and Levilactobacillus brevis DSM33325. The yogurt-style snack was characterized by protein and fiber concentration of 3 and 4%, respectively, and a low-fat content. Compared to the unfermented control, the yogurt-style snack was characterized by a significant higher concentration of free amino acids and lower contents of the antinutritional factors, i.e., phytic acid, condensed tannins, saponins and raffinose (up to 90%) mainly due to the LAB metabolic activity. Hence, an in-vitro protein digestibility of 79% and improvements of all the nutritional indexes related to the quality of the protein fraction (e.g., GABA) were achieved at the end of fermentation. According to the Harvard Medical School recommendations, the novel snack can be potentially classified as low-glycemic index food (53%). Antioxidant properties of the fermented snack were also improved by means of increased the total phenol content and radical scavenging activity. High survival rate of the starter LAB and a commercial probiotic (added to the snack) was found through 30 days storage under refrigerated conditions. The biotechnological protocol to make the novel snack here proposed is suitable for the large-scale application in food industry, giving a platform product with a peculiar and appreciated sensory profile.